Maths

Hi, can someone give me the answer to this question:
secA-tanA=1/4. Find cosA

I got: CosA=4(1-sinA) Is my answer good?




Now multply each side by (1+sinA)
CosA(1+sinA)=4 cos^2 A
CosA=1/4 (1+sinA)

16(1-sinA)=1+sinA
15=17SinA
So you have sinA, now find Cos A from your equation you originally solved.

  1. 👍 0
  2. 👎 0
  3. 👁 290
asked by Shym
  1. Cos A= 4(1-(15/17))

    cos A= 4(12/17)

    Cos A= 48/17

    1. 👍 0
    2. 👎 0
    posted by Reddy
  2. SecA+ tanA ans secA-tanA are reciprocals of each other as their product is 1.
    So secA-tanA = 1/4 means secA+tanA=4 adding, 2secA=17/4 so secA= 17/8 or cosA=8/17

    1. 👍 0
    2. 👎 0
    posted by Kelkar

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Hello I am having trouble with proving this: sinA/secA+secA/cscA = tan(A)(2-sin^2(A)) So far I've gotten SinA/(1/cosA) + (1/cosA)/(1/sinA) SinACosA + sinA/cosA I am stuck here, not even sure if multiplying by the reciprocal was

    asked by Jimbo on April 23, 2019
  2. maths(trigonometry)

    prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA

    asked by meenal on May 16, 2008
  3. Maths

    Prove that [sinA/(1-cosA)-(1-cosA)/sinA]*[cosA/(1+sinA)+(1+sinA)/cosA]=4cosecA I the second part as 2 secA

    asked by Agastya on September 15, 2016
  4. trigonometry

    if secA-tanA =10 than sinA =?,cosA =?,secA =?

    asked by Anonymous on December 23, 2016
  5. further mathematics

    Let P=(cosA sinA) (sinA cosA) Q=(cosB sinA) (sinB cosA) show that PQ=(cosA(A-B) sin(A B)) (sinA(A B) cos(A-B))

    asked by James on September 17, 2013
  6. trig

    Establish the following identity: CosA/1-TanA + SinA/1-CotA = CosA-SinA

    asked by uche on June 6, 2014
  7. mathematics trignometry

    prove that the following are identity 1. (cotA+cosecA-1)/(cotA-cosecA+1)=cosecA+cotA 2. (sinA-cosA+1)/(sinA+cosA-1)= 1/(secA-tanA)

    asked by Anonymous on March 20, 2011
  8. Trigonometry

    I need to prove that the following is true. Thanks. csc^2(A/2)=2secA/secA-1 Right Side=(2/cosA)/(1/cosA - 1) = (2/cosA)/[(1-cosA)/cosA] =2/cosA x (cosA)/(1-cosA) =2/(1-cosA) now recall cos 2X = cos^2 X - sin^2 X and we could say

    asked by Dirk on April 17, 2007
  9. maths trignometry

    Prove that. √seca+2sina/seca-2sina=Sina+cosa/sina-cosa

    asked by Aditya on September 19, 2016
  10. trig

    Match each ratio in the first row with an equivalent ratio from the second row if angle A plus angle B = 90 degrees. SinA CosA TanA CscA SecA CotA SinB CosB TanB CscB SecB CotB Does this question even make sense?

    asked by justin on April 6, 2011

More Similar Questions